Working with the inner critic in patients with depression using chairwork: a pilot study - Kroener, Julia; Mahler, Jacqueline; Sosic-Vasic, Zrinka (Frontiers in Psychiatry, 2024)
Introduction Individuals diagnosed with depression frequently experience self-criticism, leading to considerable psychological distress. Despite the availability of cognitive-behavioral treatments, a notable proportion of patients indicate that they solely experience cognitive improvements, without the corresponding emotional changes, following therapy. As a result, their psychological symptoms persist. Interventions that specifically target emotional experiencing, such as the chairwork technique, are exclusively included within long-term therapeutic procedures. Hence, the objective of this study is to assess the efficacy as well as the acceptability, feasibility, and safety of a brief intervention utilizing emotion-focused chairwork to treat self-criticism in individuals diagnosed with depression. Methods A pre-post A-B design with two post-treatment assessments (one week- and one month post-intervention) was implemented. Seven patients received three sessions of manualized emotion focused chairwork. Symptomatic change was evaluated using the Beck Depression Inventory II (BDI-II), the emotion regulation questionnaire (SEK-27), the Forms of Self-Criticizing/Reassuring Scale (FSCRS), the Self-Compassion Scale (SCS-D), as well as the Rosenberg Self-Esteem Scale (RSES). Patient satisfaction was evaluated using a self-developed questionnaire. Safety was assessed by the Beck Suicidality Inventory (BSI). Results There was a significant improvement in depressive symptoms and self-compassion at both follow-up assessment time-points. Moreover, emotion regulation as well as self-esteem improved significantly. Self-criticizing decreased significantly, while self-reassuring increased. Patients were very satisfied with the intervention. Intervention safety was given at all time-points. There were no drop-outs. Conclusion The implemented chairwork short-intervention is a feasible and safe therapeutic technique. The treatment was highly accepted revealing significant symptomatic improvements. Large-scale randomized controlled trials (RCTs) are necessary to investigate the treatment’s effectiveness.